Career Services Centre in Universities in Nigeria: Benefits and Prospects (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The implementation of a Career Service Centre (CSC) in universities in Nigeria has been a topic of interest in recent years. The need for such a center has been driven by the increasing competition and complexity of the global job market. In view of this, this paper is aims to explore the benefits of establishing career services centre in the Nigerian universities. A comprehensive analysis of existing literatures on Career Service Centre (CSC) in universities in Nigeria was done with the aid of systematic review system using secondary data that were collected from print and online publication. The paper concluded that career development, enhanced partnership between universities and private institutions, enhanced employment opportunities and support economic growth and development are the benefits establishing Career Service Centre (CSC) in the Nigerian universities. The paper also showed that Tetfund Support, Community support, Support of international organizations and private institutions are the prospects that will aid the development of the Career Service Centre (CSC) in the Nigerian universities. Based on these findings, the paper recommends that the Tetfund which is an agency of the Federal government should provide adequate funding for the implementation of Career Service Centre (CSC) in the Nigerian universities. International orgnizations and private institutions should be directly involved in the implementation of the Career Service Centre (CSC) programme. Effective capacity programme should be organize for all the universities administrators to aid effective implementation of the Career Service Centre (CSC) programme their respective institutions. Training should be organize for all the pioneering staff of the Career Service Centre (CSC) units.